New Spectrophotometric Determination of Cefdinir by Batch Method and Cloud Point Extraction - mezhir, omar qusay (Al-Mustansiriyah Journal of Science, 2019)
In this study, new spectrophotometric methods were developed for estimation of cefdinir (CFD); the research consists of two methods. The first method depends on the conversion of function group amine in cefdinir to diazonium salt and then combined with the 2, 5-Dimethylphenol (2, 5-DMP) reagent in the alkaline medium. The formed azo dye has a purple colour with absorption intensity at λmax 510 nm. Concentration range was obeyed Beer's law at (1-50 μg / ml), correlation coefficient was 0.9998, molar absorptivity was 1.54 × 104 L.mol-1.cm-1 and the detection limit was 0.04 μg.ml-1. The second method is including cloud point extraction (CPE) of a trace amount of the formed azo dye in the first method followed by measuring with a UV-visible spectrophotometer. Concentration range that obeyed the Beer's law was (0.2-6 μg / ml), correlation coefficient was 0.9998, molar absorptivity was1.48×105 L.mol-1.cm-1, detection limit was 0.004 μg.ml-1, Pre-concentration factor was 25 and Distribution coefficient was 125.The proposed methods were applied and proved their compatibility for estimating of ingredient compound in pure samples and pharmaceuticals by comparing them with previous studies.Keyword: cefdinir, diazotization, cloud point extraction, 2, 5-Dimethylphenol.